Effect of propolis on mood, quality of life, and metabolic profiles in subjects with metabolic syndrome: a randomized clinical trial - Sajjadi, Sana Sadat; Bagherniya, Mohammad; Soleimani, Davood; Siavash, Mansour; Askari, Gholamreza (Scientific reports, 2023)
Metabolic syndrome (MeS) is a common multifaceted disorder. Plants contain antioxidant bioactive compounds, which are beneficial to improve the health condition of patients with MeS. Propolis is a hive natural product that is composed of various constituent. We aimed to assess the effects of Iranian propolis as a natural and safe agent on indicators of MeS, quality of life and mood status in individuals with MeS. In total, 66 interested eligible patients recruited to the present study. Participants were randomly assigned to consume a tablet at dose of 250 mg of propolis extract, twice daily for 12 weeks or placebo. Propolis supplementation could lead to a significant reduction in waist circumference (WC), increase in physical functioning, general health and the overall score of SF-36 compared with placebo group (P-value < 0.05). However, no significant differences were observed regarding other anthropometric indices and biochemical parameters between two groups (P-value > 0.05). The current study indicated that propolis can be effective in decreasing WC and improving physical health and quality of life, while had no significant effects on other components of MeS among subjects with this syndrome. Clinical trials registration Iran Registry of Clinical Trials.ir IRCT20121216011763N49, registration date 23/12/2020.